2023
DOI: 10.1021/acscatal.3c02649
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Oxygen Vacancies for Enhanced Higher Oxygenate Synthesis via Syngas

Xingzhen Qi,
Tiejun Lin,
Yunlei An
et al.

Abstract: Constructing highly efficient dual active sites for preferential formation of higher oxygenates via direct syngas conversion remains a grand challenge. Herein, we reported that the regulation of oxygen vacancy density of metal–oxide support could effectively promote the production of oxygenates. Compared with an inert SiO2-supported Co-based catalyst, the rutile TiO2-supported catalyst with abundant oxygen vacancies exhibited up to 44.7% CO conversion with the selectivity and space–time yield (STY) of the oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 66 publications
2
1
0
Order By: Relevance
“…EPR characterization was also tested and is shown in Figure S5. A symmetrical signal with a g value of 2.004 was detected for all spent catalysts, which confirmed the existence of oxygen vacancies . The intensity of the EPR signal represents the density of oxygen vacancies, and the changing trend of different samples is consistent with the fitted results of the O 1s XPS spectra.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…EPR characterization was also tested and is shown in Figure S5. A symmetrical signal with a g value of 2.004 was detected for all spent catalysts, which confirmed the existence of oxygen vacancies . The intensity of the EPR signal represents the density of oxygen vacancies, and the changing trend of different samples is consistent with the fitted results of the O 1s XPS spectra.…”
Section: Resultssupporting
confidence: 80%
“…A symmetrical signal with a g value of 2.004 was detected for all spent catalysts, which confirmed the existence of oxygen vacancies. 39 The intensity of the EPR signal represents the density of oxygen vacancies, and the changing trend of different samples is consistent with the fitted results of the O 1s XPS spectra. The C 1s XPS spectra was fitted at 284 and 284.8 eV, which are attributed to the carbide species of Co 2 C and −(CH 2 ) n −, respectively, 17,40,41 further suggesting the formation of carbides during the reaction.…”
Section: Structural Properties and Morphology Of The Spent Comnosupporting
confidence: 84%
“…10–13 The application of the SMSI effect in enhancing catalytic reactivity and product selectivity of a metal catalyst has been commonly reported for CO hydrogenation toward long-chain hydrocarbons. 14–18 Zhang et al reported that the activity in FTS shows a volcano-like trend with increasing reduction temperature from 200 to 600 °C. 14 Such a variation in activity is characterized as being related to the as-formed metal–support interface, in which the TiO x overlayer at Ru/TiO 2 interfaces promotes CO dissociation.…”
Section: Introductionmentioning
confidence: 99%